SARS-CoV-2 viral RNA biology and its impact on the infected cell - Altina, Noelia H., author; Wilusz, Jeffrey, advisor; Argueso, Lucas, committee member; Geiss, Brian, committee member; Perera, Rushika, committee member; Yao, Tingting, committee member (Colorado State University. Libraries, 2023)
The fine-tuning of the replication and transcription of RNA viruses often requires the interaction of viral RNAs with cellular RNA binding proteins. This project addresses fundamental knowledge gaps on the molecular mechanisms that underlie SARS-CoV-2 gene expression, regulation, and viral RNA-host interactions. After infection, SARS-CoV-2 generates a large set of sub-genomic mRNAs, each containing an identical ~70 base 'leader' region in their 5'UTR (from position 14 to position 75 in RefSeq NC_045512) and a 229 base region at the 3'UTR (from position 29,675 to position 29,903 in RefSeq NC_045512) generated by discontinuous transcription. The accumulation of a considerable amount of these leader/3'UTR regions during the infection represents a possible sink for cellular RNA binding proteins. We demonstrated that PTBP1, a cellular protein involved in the regulation of alternative splicing, binds to the SARS-CoV-2 leader region. SARS-CoV-2 infection critically impacted the splicing of several cellular pre-mRNAs that are normally regulated by PTBP1. Mechanistically, we suggest that SARS-CoV-2 sequesters and influences the re-localization of shuttling splicing factors like PTBP1 from the nucleus to the cytoplasm resulting in significant effects on the host cell splicing machinery leading to changes in cellular mRNA splicing patterns during SARS-CoV-2 infection. Given the current extensive interest in epigenetic methylations of both cellular and viral RNAs, our study also explored the role of post-transcriptional RNA modifications on viral mRNAs. We demonstrated that SARS-CoV-2 can usurp the cellular enzyme, namely PCIF1, to place the m6Am modification at the cap proximal position in its mRNAs. This double methylation is usually found on all host mRNAs that initiate with an adenosine residue, and thus SARS-CoV-2 likely installs this modification on its mRNAs to avoid host immune recognition. Interestingly, we also discovered that capping and m6Am modification are tightly regulated throughout the infection. The highest levels of these 5' end RNA modifications were observed at 12 hours post infection, correlating with the full establishment of viral gene expression in infected cells. These findings indicate that 5' end modification of SARS-CoV-2 transcripts is not simply a default process but rather undergoes unanticipated regulation throughout the infection. Collectively, the data presented provide not only new insights into the complex interactions that SARS-CoV-2 has with the RNA biology of the cell during infection, but also identify attractive potential targets for developing novel anti-coronavirus drugs to treat future emerging coronavirus diseases.
Keywords: m6A; RNA; splicing; PTBP1; capping; SARS-CoV-2